Fluctuations in pelagic fish density linked to ambient conditions. Issue 3 (9th December 2020) - Holubová, Michaela; Hejzlar, Josef; Čech, Martin; Vašek, Mojmír; Blabolil, Petr; Peterka, Jiří
Abstract: Animal behaviour has been broadly studied for its social or functional aspects but less often for understanding the interactions between organisms and their ambient conditions. A pilot observational study was performed by means of underwater camera to investigate the correlation between environmental factors and the density of fish in the epipelagic habitat of a European temperate reservoir. Explored factors confirmed a positive correlation between water temperature and all observed categories: nonpredatory, predatory, single nonpredatory and schooling fish, as well as freshwater bream and roach. On the other hand, de‐trended solar irradiance was found to be negatively correlated with density of nonpredatory fish, freshwater bream and European perch. Sunshine duration was negatively correlated with the density of predatory fish. Precipitation a showed positive relationship with single nonpredatory fish and European perch, whereas wind strength had a negative relationship with density of schooling fish. Furthermore, density of predatory fish was positively correlated with density of single nonpredatory fish and counts of observed clusters. Altogether, findings indicate that fish density is correlated with abiotic factors and the occurrence of predators. This suggests that more ecologically complex studies should be encouraged for better understanding of ecological interactions that drive the structure of aquatic ecosystems.